Evaluation of the results of occupational medical examinations of hearing loss in workers of a textile dyeing plant in Lima - Garro A., Evelyn J. (2020)
The objective of this study is to determine the level of association of the physical noise risk factor that derives as occupational disease from hearing loss in a textile dry cleaning plant, located in Los Olivos, Lima, in 2014 and 2017; It is a non-experimental, quantitative correlational design investigation, to determine the sample of workers, the Sierra Bravo formula was used to determine the occupational medical exams of 91 workers, the data were analyzed using the statistical program SPSS Statistics version 24, and the non-linear canonical correlation analysis, multivariate statistical method. The results indicate a level of significance alpha = 0.05 at 95% confidence. Concluding that there is an association of the physical risk factor noise with hearing loss as an occupational disease in a textile plant, case of the textile plant located in Los Olivos, 2014-2017 period; Recommending to take corrective measures based on the results of the pre-occupational and periodic medical examinations and of the prevention programs of risks to the Occupational Health of the workers in the textile dyeing factories.